Microchannel flow and heat transfer enhancement via ribs arrangements. (April 2022) - Ebaika, Johnny Adukwu; Shuja, S. Z.; Yilbas, B. S.; Al-Qahtani, H.
Enhanced heat transfer rates in microchannel flow remain challenging in terms of channel design, proper selection of carrier fluid, and setting the appropriate flow conditions. Introducing extended surfaces, such as ribs, in microchannel design, and the use of nanofluids enable to enhance the thermal performance of the flow system. In the present study, heat transfer characteristics in a microchannel flow incorporating the ribs arrangements on the channel wall are considered and the influence of the ribs location and carrier fluid on the thermal performance of the channel is examined. Temperature and velocity variations in the channel are predicted numerically and the findings of the Nusselt number are compared with that obtained from the experiments. The location of ribs along the channel wall is altered and the resulting variation of the Nusselt number and pressure drop along the microchannel is assessed. Al2 O3 and TiO2 nanofluids are incorporated as a working fluid and water are also considered for the comparison. Temperature parameters are introduced to scale the rise of the maximum fluid temperature and temperature difference across the channel length. It is found that locating the ribs in the close region of the channel exit improves the Nusselt number by 25% and increases the pressure drop along the microchannel by 10% as compared to those corresponding to no-ribs arrangements. In addition, nanofluids improve the heat transfer rates and slightly alter the pressure drop across the microchannel.